2004
DOI: 10.1136/bmj.38106.559120.7c
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up study of survival associated with cleft lip and palate at birth

Abstract: Objective To assess the overall and cause specific mortality of people from birth to 55 years with cleft lip and palate. Design Long term follow up study. Setting Danish register of deaths. Participants People born with cleft lip and palate between 1943 and 1987, followed to 1998. Main outcome measures Observed and expected numbers of deaths, summarised as overall and cause specific standardised mortality ratios. Results 5331 people with cleft lip and palate were followed for 170 421 person years. The expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
188
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(195 citation statements)
references
References 13 publications
1
188
1
2
Order By: Relevance
“…No studies have reported the impact of clefting on the quality of life of infants. Survival in association with clefting has also been assessed, and recent work suggests that there may be an overall increase in mortality from all causes, with suicide as a single significant contributor; this is consistent with concerns about psychological adjustment (Christensen et al, 2004).These findings indicate that there may be a relative burden of oral clefting on the overall quality of life across all age groups. However, no previous studies have attempted to directly measure preferences related to oral clefting as a health state and to provide HRQL scores that could be used in evaluating the effectiveness and cost effectiveness of health interventions and prevention programs aimed at clefting.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…No studies have reported the impact of clefting on the quality of life of infants. Survival in association with clefting has also been assessed, and recent work suggests that there may be an overall increase in mortality from all causes, with suicide as a single significant contributor; this is consistent with concerns about psychological adjustment (Christensen et al, 2004).These findings indicate that there may be a relative burden of oral clefting on the overall quality of life across all age groups. However, no previous studies have attempted to directly measure preferences related to oral clefting as a health state and to provide HRQL scores that could be used in evaluating the effectiveness and cost effectiveness of health interventions and prevention programs aimed at clefting.…”
supporting
confidence: 62%
“…No studies have reported the impact of clefting on the quality of life of infants. Survival in association with clefting has also been assessed, and recent work suggests that there may be an overall increase in mortality from all causes, with suicide as a single significant contributor; this is consistent with concerns about psychological adjustment (Christensen et al, 2004).…”
Section: Nih Public Accessmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent work suggested that there has been a gross underestimation of the consequences of being born with CL/P (1). Individuals born with CL/P have a shorter lifespan, with increased risk for all major causes of death, when compared with individuals born without clefts (5). Contributing to these higher mortality rates are probably psychiatric disorders and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Children with nonsyndromic clefts are at increased risk for mild delays in some developmental areas (Nopoulos et al, 2002(Nopoulos et al, , 2005 and learning disabilities (Broder et al, 1998). They also have a lifetime risk for increased mortality across all causes, with suicide as a specific risk (Christensen et al, 2004).…”
mentioning
confidence: 99%